Effect of Exchange Actions on the Frosty Texture of Deposits and the Structure of Segregated Ice - Konnova,O. S. (1970)
The data received shows that the structure of segregated ice, its crystallographic orientation, as well as the intensity of the ice formation and nature of growth of the ice inclusion, are in direct relationship to the physico-chemical properties of the freezing soil. Three types of frosty texture and structure of segregated ice have been established in relationship to the physico-chemical properties in freezing soil. (Author) Trans. of Akademiya Nauk SSSR. Institut Merzlotovedeniya. Materialy po Laboratornym Issledovaniyam Merzlykh Gruntov, n4 p53-80 1961.